Reversible α‐Hydrogen and α‐Alkyl Elimination in PC(sp3)P Pincer Complexes of Iridium1. Issue 32 (26th June 2015) - Jonasson, Klara J.; Polukeev, Alexey V.; Marcos, Rocío; Ahlquist, Mårten S. G.; Wendt, Ola F.
Abstract Despite significant progress in recent years, the cleavage of unstrained C(sp3)C(sp3) bonds remains challenging. A CC coupling and cleavage reaction in a PC(sp3)P iridium pincer complex is mechanistically studied; the reaction proceeds via the formation of a carbene intermediate and can be described as a competition between α‐hydrogen and α‐alkyl elimination; the latter process was observed experimentally and is an unusual way of C(sp3)C(sp3) bond scission, which has previously not been studied in detail. Mechanistic details that are based upon kinetic studies, activation parameters, and DFT calculations are also discussed. A full characterization of a CC agostic intermediate is presented.